Caching of XML Web Services for Disconnected Operation - Ramasubramanian, Rama; Terry, Doug (2004)
Caching can permit mobile applications to utilize XML Web services in the face of intermittent connectivity. However, Web services present a number of challenges to cache managers since they have generally been designed without regard to caching and hence provide little support. The WSDL description of a Web service, for instance, specifies the SOAP message formats needed to invoke service operations but does not indicate which operations modify the service’s persistent state or will likely produce different results on different invocations. We developed tools for generating custom cache managers that tailor their behavior based on annotations added to a Web service’s WSDL specification. An experiment to transparently interject a cache between existing XML Web services and their clients running on mobile devices demonstrated that disconnected operation could be achieved without modifying services or their applications.
This is an expanded version of an article that appeared in ACM Queue.